2003
DOI: 10.1046/j.1468-1331.2003.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of repetitive transcranial magnetic stimulation on motor function in Parkinson's disease patients

Abstract: Cortical excitability of the primary motor cortex is altered in patients with Parkinson's disease (PD). Therefore, modulation of cortical excitability by high frequency repetitive transcranial magnetic stimulation (rTMS) of the motor cortex might result in beneficial effects on motor functions in PD. The present study aims to evaluate the effect of rTMS of the motor cortex on motor functions in patients with PD. Thirty-six unmedicated PD patients were included consecutively in this study. The patients were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
2
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(164 citation statements)
references
References 26 publications
(36 reference statements)
7
145
2
6
Order By: Relevance
“…When this current is applied repetitively, repetitive transcranial magnetic stimulation (rTMS), it can modulate cortical excitability, decreasing or increasing it, depending on the parameters of stimulation. Since its inception, researchers have proposed the use of TMS and rTMS to study and treat neuropsychiatric diseases, such as major depression George et al 2000;Martin et al 2003;Holtzheimer et al 2004;Rumi et al 2005), schizophrenia (Hoffman et al 2003;Lee et al 2005), Parkinson's disease (Mally and Stone 1999;de Groot et al 2001;Khedr et al 2003;Fregni et al 2004;Lefaucheur et al 2004), dystonia (Huang et al 2004), epilepsy (Tergau et al 1999;Menkes and Gruenthal 2000;Daniele et al 2003;Fregni et al 2005) and the acute or chronic sequels derived from stroke ). However, a fundamental question that needs to be addressed before the wide-spread use of TMS in clinical practice, is how the modification of brain anatomy and tissue properties caused by certain neuropsychiatric diseases can alter the effects of TMS.…”
Section: Introductionmentioning
confidence: 99%
“…When this current is applied repetitively, repetitive transcranial magnetic stimulation (rTMS), it can modulate cortical excitability, decreasing or increasing it, depending on the parameters of stimulation. Since its inception, researchers have proposed the use of TMS and rTMS to study and treat neuropsychiatric diseases, such as major depression George et al 2000;Martin et al 2003;Holtzheimer et al 2004;Rumi et al 2005), schizophrenia (Hoffman et al 2003;Lee et al 2005), Parkinson's disease (Mally and Stone 1999;de Groot et al 2001;Khedr et al 2003;Fregni et al 2004;Lefaucheur et al 2004), dystonia (Huang et al 2004), epilepsy (Tergau et al 1999;Menkes and Gruenthal 2000;Daniele et al 2003;Fregni et al 2005) and the acute or chronic sequels derived from stroke ). However, a fundamental question that needs to be addressed before the wide-spread use of TMS in clinical practice, is how the modification of brain anatomy and tissue properties caused by certain neuropsychiatric diseases can alter the effects of TMS.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the magnitude of effects varied significantly across studies, probably due to the heterogeneity between stimulation protocols (in terms of frequency, intensity, duration) and targeted regions. Moreover, many studies were not sham-controlled and for sham-controlled studies, different methods of sham stimulation have been used: tilted [33,37,54,56,60,62], sham [39,47,63] and inactive coils [50,66,68] have been used, as well as occipital stimulation [40,49,61], coil back surface [41] and realistic sham [51,57,58]. A very recent review [69] examined 20 RCTs of rTMS treatment for motor dysfunction in PD to evaluate the efficacy of treatment and identify protocols factors that moderate the effects of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies [32][33][34]39,45,52,54,55,63] tested the effects of only one rTMS session, while the remaining administered a higher number of sessions, ranging from 2 to 20. Most studies, especially those targeting M1, SMA and DLPFC, administered high-frequency stimulation (24 of 40 studies) [29][30][31][32][33][34][37][38][40][41][42][43][44][49][50][51][53][54][55][57][58][60][61][62], while lowfrequency stimulation was employed primarily in studies targeting other regions. The intensity of stimulation ranged from 20% of motor threshold to 120%.…”
Section: Rtms Studies In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated 25 Hz rTMS of M1 (Khedr, Rothwell, Shawky, Ahmed, & Hamdy, 2006) and combined M1 and DLPFC (M. P. Lomarev et al, 2006), suprathreshold 5 Hz rTMS (120% RMT, 10 sessions) of M1 (Khedr, Farweez, & Islam, 2003) and of SMA (at 110% AMT) (Hamada, Ugawa, Tsuji, & Effectiveness of rTms on Parkinson's Disease Study Group, 2008), and anodal tDCS of motor and prefrontal cortices (Benninger et al, 2010), have shown the strongest therapeutic efficacy. In contrast, iTBS of M1 and DLPFC (Benninger et al, 2011), and 0.2 Hz rTMS (110% RMT) (Okabe, Ugawa, Kanazawa, & Group, 2003) and 50 Hz rTMS (80% AMT) (Benninger et al, 2012) of M1, all failed to improve motor symptoms.…”
Section: Current Concepts Of Non-invasive Brain Stimulation In Parkinmentioning
confidence: 99%